Marine Biotoxins in shellfish: Brevetoxin (A Review) - Muhammad Alfid Kurnianto; Rahmawati Rahmawati (Future Science, 2022)
Molluscan shellfish can accumulate natural poison produced by marine algae, one of which is brevetoxin (BTx). BTx is a toxin produced by marine dinoflagellates of the Karenia genus, especially Karenia brevis, which has the characteristics of being fat-soluble, lipophilic, colorless, tasteless, and very heat stable. Based on the backbone structure, BTx is classified into BTx-1 and BTx-2. BTx-2 is the most common type of toxin produced by K. brevis. BTx was synthesized from a polyketide synthase pathway that could potentially incorporate larger carbon units of acetate modified by the citric acid cycle. BTx poisoning causes neurologic shellfish syndrome (NSP), which is characterized by major symptoms in the neurological and gastrointestinal systems. NSP is due to the high affinity of BTx in binding to receptors on the cell wall, namely voltage-gated sodium channels (NaV). Based on the food safety risks posed, monitoring programs to detect the growth of harmful algae and the presence of brevetoxin in food should be implemented. Several detection methods have been developed, such as mouse bioassay, cytotoxicity assay, receptor binding assay, immunoassay and LC-MS/MS.